Reconstructing State Financial Audit Authority Post-Constitutional Court Decision No. 28/PUU-XXIV/2026 - Noor, Aslan; Rizaldi, Dea Eka; Suprianto, Yusup; Irawan, Andri; Adeffian, Choirul (Fakultas Syariah INSURI Ponorogo, 2026)
Indonesia's constitutional framework assigns the Financial Audit Agency (BPK) an exclusive audit mandate under Article 23E (1) of the 1945 Constitution. However, persistent institutional dualism has allowed bodies such as BPKP and APIP to calculate state financial losses in corruption proceedings, thereby generating fundamental legal uncertainty. The normative ambiguity of Articles 603 and 604 of Law Number 1 of 2023 on the Criminal Code, which fail to designate the authorized institution or measurement standard for state losses. This study examines how audit authority may be defined in terms of normative criteria and the implications of Constitutional Court Decision Number 28/PUU-XXIV/2026 for Indonesia's state financial accountability system. A normative legal method is employed, combining statutory, conceptual, and case approaches with systematic, teleological, and historical interpretation. The study finds that the audit authority is of an attributive-constitutional character, grounded exclusively in Article 23E. The decision institutionally repositions BPKP and APIP as internal oversight bodies, procedurally obligates law enforcement to rely on BPK findings, and constitutionally reinforces legal certainty under Article 28D paragraph (1). This study contributes to the concept of constitutionalization of audit authority as a framework for understanding how independent oversight institutions are embedded within and protected by the constitutional order.